VD_FINDINFO HC / 2012 / 433 vom 28. Juni 2012 - VD Tribunal cantonal (2012)
OBLIGATION D'ENTRETIEN, RENTE D'INVALIDITÉ, REVENU HYPOTHÉTIQUE | 176 al. 1 ch. 1 CC, 308 al. 1 let. b CPC (CH), 314 al. 1 CPC (CH)